The Defining Moment: A Review Essay - Ohanian, Lee E. (Journal of Political Economy, 1999)
This article reviews The Defining Moment, edited by Michael D. Bordo, Claudia Goldin, and Eugene N. White. The volume studies how the Great Depression changed government policies, including changes in monetary policy, fiscal policy, banking policy, agricultural policy, social insurance, and international economic policy. I argue that a theory of policy evolution is required to answer how the Great Depression affected these policies. In the absence of this theory, the contributors provide insight into the question by showing how policies changed sharply in the 1930s with little or no historical precedent or by showing how policies were tied to political or other considerations unique to the period. While this volume does not always provide answers to the questions posed, it does raise a fundamental issue in the analysis of government policy: Why during some crisis periods are bad policies adopted, whereas during other periods they are not ?